Revisiting the role of interfacial chemistry in composite durability: Recent concepts and developments - Khan Ahmadi, Faezeh (Journal of Composites and Compounds, 2024)
This paper investigates the role of interfacial structures and chemistry in the durability and mechanical performance of fiber-reinforced composite materials. First, the history and development trend of hybrid composites are reviewed, and then the types of bonding in polymer and metal composites are analyzed. Next, nanoscale features such as nanopores and nanofibers and the principles of nano-structuring in the interfacial region are reviewed. The paper compares the effects of matrix changes and interfacial nanostructure engineering on the mechanical behavior of nanocomposites and finally, presents a nonlinear damage model to describe deformation in polymer nanocomposites, which is applied to epoxy systems containing carbon nanotubes and reactive graphite.